Traditional Art in Minangkabau Culture - Rustim; Irwan; Ernawita; Yusnelli (Kirana Publisher (KNPub), 2023)
Minangkabau society adheres to philosophies as conceptions that are implied into its culture, one of which is the presence of art. Art in Minangkabau culture lives and develops with the passage of time and the creativity of the people is dynamic. This research is a type of qualitative research by observing the arts, especially those related to traditions in the culture of the Minangkabau people using the Hermeneutic approach and literature study. The research was conducted by observing the forms of Minangkabau traditional art, especially traditional music and its development in Minangkabau society. The results and discussion of this research include; forms of Minangkabau traditional art and art in Minangkabau culture.